Moderate innovator trap - does the convergence of innovation performance occur in the world economy? - Arkadiusz Michał Kowalski; Jakub Rybacki (Economies, 2021)
Based on ß and o convergence analysis, we find a high persistence of innovation gaps for international innovation indices reported by the European Commission. Our research confirms the diverging scientific potential across the analyzed economies. Estimation provides evidence of convergence in the case of R&D expenses and the relative position on the global technological frontier. We propose a simple fixed effect panel regression measuring relative innovativeness potential. Our model suggests that current ranking leaders, i.e., Nordic countries (Sweden, Denmark, and Finland) and Germany, are likely to further outpace the United States. Central and Eastern European countries are achieving the greatest relative gains but are unlikely to exceed 70% of US potential. Peripheral European countries, South Africa, Turkey, and Russia are projected to further lose their innovativeness position despite their weaker initial position.
Keywords: 330; ß convergence; o convergence; innovation; moderate innovators